Assessing soil quality issues for crop production function based on farmers’ perception: An experience from Itapaji Watershed in Southwestern Nigeria - Olateju Dolapo Adeyolanu; Kayode Stephen Are; Ayodele Olumide Adelana; Gabriel Akinboye Oluwatosin; Oluwabunmi Aderonke Denton; Olufunmilayo Titilayo Ande; Olugbenga Egbetokun; Lucia Ogunsumi; James Alabi Adediran (Eurasian Journal of Soil Science, 2018)
To successfully manage soil quality for sustainable crop production, there is need to identify issues affecting it. These are problems facing the capacity of soil to perform its functions and thus reducing its productivity. In addition, the similarities and differences between farmers’ perception of soil quality issues and that of soil scientist are very pertinent. This study, which was carried out at Itapaji watershed in Ikole local government area of Ekiti state, aims at identifying soil quality issues using participatory approach and conventional method. Diagnostic survey was carried out using participatory approach involving farmers’ judgement using questionaires. . The resultswere analysed to identify the soil quality issues from farmers’ perspectives. For conventional method, major soil types were identified and soil quality issues were identified using soil management assessment framework. The relationship between the soil issues from farmers’ interview and soil analysis were established by correlation analysis at α0.05. Soil quality issues identified by farmers are soil compaction, low soil fertility, termite infestation, crop wilt, hardpan formation, erosion, poor drainage and land use intensification. Low soil fertility is the most prominent with about 36.2 % impact on crop production in the watershed. Conventionally from soil analysis, CEC and organic matter are low which indicate low soil fertility; there is high acidity, shallow soil depth with presence of plinthite and hard pan. The farmers’ perception of soil quality and that of soil scientists correlate well (r = 0.70). There is therefore need for promotion of farmers’ participation by providing a forum for articulation of their opinions in mitigating low soil quality.